The Effect of Using Project Methods and Lecture Methods on Early Childhood Science Knowledge in Nurul Iman Islamic Kindergarten Karanganyar Academic Year 2020/2021 - Suci Indah Sayekti; Sukamdi; Latifah Permatasari fajrin (ABNA : Journal of Islamic Early Childhood Education, 2022)
ABSTRACT The problem in this study is the ability to recognize color mixing in children is still low. The purpose of this study was to determine the effect of using the project method and the lecture method on early childhood science knowledge. This research used experimental quantitative research, carried out at Nurul Iman Islamic Kindergarten Karanganyar in July-November 2020. The population in this study were 53 B grade children in Islamic Kindergarten. Nurul Iman Karanganyar, a sample of 17 children. The sampling technique in this study used a simple random sampling technique. The data collection method used a test in the form of a project carried out by children. Data analysis used unit analysis and prerequisite tests, namely normality test, homogeneity test, and hypothesis testing. The results showed that there were differences in the effect of using the project method on early childhood science knowledge in Nurul Iman Islamic Kindergarten Karanganyar. The project method has an effect on early childhood science knowledge, with the project method the average score is 21.35, which is greater than the lecture method, the average value is 15.47. Keywords: Project Method, Science Knowledge and Early Childhood   Abstrak Permasalahan dalam penelitian ini adalah kemampuan mengenal pencampuran warna pada anak masih rendah. Tujuan penelitian ini untuk mengetahui pengaruh penggunaan metode proyek dan metode ceramah terhadap pengetahuan sains anak usia dini Penelitian ini menggunakan penelitian kuantitatif eksperimen, dilaksanakan di TK Islam Nurul Iman Karanganyar pada Juli-November 2020. Populasi dalam penelitian ini adalah 53 anak kelas B di TK Islam Nurul Iman Karanganyar, sampel 17 anak. Teknik sampling dalam penelitian menggunakan teknik sampling simple random sampling. Metode pengumpulan data menggunakan tes berupa proyek yang dilakukan anak. Analisis data menggunakan analisis unit dan uji prasyarat yaitu uji normalitas, uji homogenitas, dan uji hipotesis. Hasil penelitian menunjukkan bahwa terdapat perbedaan pengaruh penggunaan metode proyek terhadap pengetahuan sains anak usia dini di TK Islam Nurul Iman Karanganyar. Metode proyek berpengaruh pada pengetahuan sains anak usia dini, dengan metode proyek diperoleh nilai rata-rata 21,35 lebih besar dari metode ceramah diperoleh nilai rata-rata 15,47. Kata Kunci : Metode Proyek, Pengetahuan Sains dan Anak Usia Dini